2020
DOI: 10.3389/fimmu.2020.00268
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte-Mediated Phagocytosis in Crustaceans

Abstract: Phagocytosis is an ancient, highly conserved process in all multicellular organisms, through which the host can protect itself against invading microorganisms and environmental particles, as well as remove self-apoptotic cells/cell debris to maintain tissue homeostasis. In crustacean, phagocytosis by hemocyte has also been well-recognized as a crucial defense mechanism for the host against infectious agents such as bacteria and viruses. In this review, we summarized the current knowledge of hemocyte-mediated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…Phagocytosis is a crucial defense mechanism against bacteria and viruses in shrimp. Many types of genes are involved in phagocytosis, such as receptors for recognition, downstream signal pathways, and intracellular regulators ( Liu et al, 2020 ). In kuruma shrimp M. japonicus , integrin alpha PS is reported as a marker for hemocytes that mediates phagocytosis ( Koiwai et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phagocytosis is a crucial defense mechanism against bacteria and viruses in shrimp. Many types of genes are involved in phagocytosis, such as receptors for recognition, downstream signal pathways, and intracellular regulators ( Liu et al, 2020 ). In kuruma shrimp M. japonicus , integrin alpha PS is reported as a marker for hemocytes that mediates phagocytosis ( Koiwai et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In kuruma shrimp M. japonicus , integrin alpha PS is reported as a marker for hemocytes that mediates phagocytosis ( Koiwai et al, 2018 ). However, it is reported that different subpopulations of hemocytes seem to exhibit specific preferences of different bacteria or viruses in phagocytosis ( Liu et al, 2020 ). Since there are many cascades for phagocytosis and various molecules work together, it is difficult to determine which cluster is centralized, but various phagocytosis-related genes are expressed relatively strongly in Hem 5 ( Figure 8—figure supplement 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cytoskeletal proteins, including myosin regulatory light chain (MRLC), myosin light chain (MLC), and tubulin α and β chains, were found to be significantly upregulated after M. bicuspidata infection. It is well known that cytoskeletal proteins are essential for phagocytosis, which is an important innate immune response of crustaceans ( 28 , 29 ). The basic structure of myosin in vertebrate and invertebrate muscles is identical.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the CTLs, the I-type lectin hemolin SeHem from S. exigua also helped the host cells to eliminate bacteria by enhancing phagocytosis [62]. Galectins from crustaceans have been reported to enhance host phagocytosis [107] but there are no such reports for insect galectins.…”
Section: Lectin-induced Cellular Immunity 421 Phagocytosismentioning
confidence: 99%